Little darlings - Golding, Melanie (Crooked Lane, 2019)
Lauren Tranter knows what she saw: in her hospital room, a woman tried to take her newborn twins and replace them with her own creatures. Everyone thinks she's imagining things. A month passes-- and one morning the babies disappear from Lauren's side in a park. When they're found, something is different about them. The infants look like Morgan and Riley-- to everyone else. But to Lauren, something is off. Determined to bring her true infant sons home, Lauren will risk the unthinkable. -- adapted from jacket